Design is storytelling - Lupton, Ellen, 1963- (New York : Cooper-Hewitt, 2017)
A playbook for creative thinking, created for contemporary students and practitioners working across the fields of graphic design, product design, service design and user experience. Design is Storytelling is a guide to thinking and making created for contemporary students and practitioners working across the fields of graphic design, product design, service design, and user experience. By grounding narrative concepts in fresh, concrete examples and demonstrations, this compelling book provides designers with tools and insights for shaping behaviour and engaging users. Compact, relevant and richly illustrated, the book is written with a sense of humour and a respect for the reader's time and intelligence. Design is Storytelling unpacks the elements of narrative into a fun and useful toolkit, bringing together principles from literary criticism, narratology, cognitive science, semiotics, phenomenology and critical theory to show how visual communication mobilizes instinctive biological processes as well as social norms and conventions. The book uses 250 illustrations to actively engage readers in the process of looking and understanding. This lively book shows how designers can use the principles of storytelling and visual thinking to create beautiful, surprising and effective outcomes. Although the book is full of practical advice for designers, it will also appeal to people more broadly involved in branding, marketing, business and communication.
Keywords: Graphic design; Productdesign; Productontwerpen